PELATIHAN VIDEO EDITING TINGKAT SMK SE-KOTA SINGARAJA - Sugihartini, Nyoman; Agustini, Ketut; Pradnyana, I Made Ardwi (Universitas Pendidikan Ganesha, 2017)
The purpose of this P2M activity is to improve the understanding, knowledge and skills of SMK students in video editing at Singaraja city. The implementation of P2M activities is conducted for one day, with details of the activities include: (1) Opening by the Dean conducted in the room of the Faculty of Engineering and Vocational. (2) Video editing training conducted in Laboratory of Culture Department of Informatics Engineering Education. Implementation of the training include: the introduction of Adobe Premiere tools, Steps to do video editing, making a simple project and closed with discussions related to the project that has been made. The result of this devotional activity is a simple project created by the trainees. This activity has contributed to the students of vocational school level as Singaraja city that is in the form of knowledge and skill.